Standardization of In-vivo Nitrate Reductase Activity in Clitoria ternatea L. Leaves - Chaukiyal, S. P. (Indian Forester, 2008)
The combination of different concentrations of substrate (0.10M, 0.15M, 0.20M and 0.25M; KNO3) with different pH of buffer (0.2M KH2PO4, pH 6.5, 7.0, 7.5, 7.6, 7.7, 7.8, 7.9 and 8.0) solution were tried for the nitrate reductase activity of Clitoria ternatea L. leaves. Maximum nitrate reductase activity was observed in the combination of buffer solution of 0.20M having pH 7.5 and substrate solution of the concentration 0.20M.